1991
DOI: 10.1021/je00003a012
|View full text |Cite
|
Sign up to set email alerts
|

Liquid-liquid equilibria for ternary systems formed by acetonitrile, water, and aromatic hydrocarbons

Abstract: Liquid-liquid equilibria were measured at 25 and 45 °C for the ternary systems formed by acetonitrile + water + an aromatic hydrocarbon (benzene, toluene, m-xylene, p-xylene, ethylbenzene). Type I Isotherms were observed for the five systems both at 25 and at 45 °C. The binodal curves and tie lines may be predicted by using the NRTL model on the basis of parameters found from binary data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 4 publications
2
6
0
Order By: Relevance
“…The ternary liquid–liquid equilibria of the MeCN–water–toluene system at 20 °C is shown in Figure , illustrating typical Type I phase behaviour. The figure also shows good agreement between data obtained in this experimental study, COSMO-RS prediction- and previously reported data for the ternary system.…”
Section: Case Study On the Recovery Of Mecn From The Mecn–water–tolue...supporting
confidence: 90%
“…The ternary liquid–liquid equilibria of the MeCN–water–toluene system at 20 °C is shown in Figure , illustrating typical Type I phase behaviour. The figure also shows good agreement between data obtained in this experimental study, COSMO-RS prediction- and previously reported data for the ternary system.…”
Section: Case Study On the Recovery Of Mecn From The Mecn–water–tolue...supporting
confidence: 90%
“…LLE of investigated water–toluene systems at T = 298.15 K and p = 101.3 kPa: (I) water + toluene + acetone (System I); (II) water + toluene + ethanol (System II); (III) water + toluene + tetrahydrofuran (System III); (IV) water + toluene + acetonitrile (System IV). Dash-dotted lines with open symbols are tie lines taken from literature (I, II, III, IV,) straight lines with filled symbols are experimental tie lines from this work (Table ), dashed lines are binodal curve, and their corresponding tie lines are calculated by the KK model. Model parameters are presented in Table .…”
Section: Resultsmentioning
confidence: 97%
“…Dash-dotted lines with open symbols are tie lines taken from literature (I,34 II,35 III,36 IV,37 ) straight lines with filled symbols are experimental tie lines from this work (Table2), dashed lines are binodal curve, and their corresponding tie lines are calculated by the KK model. Model parameters are presented in Table3.…”
mentioning
confidence: 99%
“…While the accuracy of this method is diminished compared to traditional tie-line measurements of biphasic systems, we were able to show that the data achieved using this technique is comparable to data reported in literature using conventional measurement techniques. 3 In these ternary combinations, the number of components involved in any experiment is three (aqueous, organic, and antisolvent). However, the number of available phases is assumed to be two (two distinct liquid phases; the vaporization of organics and water was assumed to be negligible for the purposes of these scoping experiments).…”
Section: Srnl-sti-2020-00426 Ldrd Reportmentioning
confidence: 99%